Is deliberation a laudable goal when policy is a done deal? The Habermasian public sphere and legitimacy in a market era of education policymaking - Liza N. Pappas (Arizona State University, 2016)
The state mandated public hearings concerning school closing proposals in New York City provide a window into a diverse set of policy actors and their deliberations. Opposition to school closures is often cast as entrenched interests, emotional attachment, support for the status quo or at worst negligence. However, content analysis reveals that testimony offered by parent, community, and educator leaders contained a range of substantial critiques of school closing proposals, their motivations, justifications, and expected results. I argue that the hearings did not fully constitute a public sphere by Habermasian criteria, nor a counterpublic by Fraser and Dawson criteria. In fact, the hearings had contradictory effects; one school successfully fought closure by both resisting and reifying neoliberal logic in education policymaking. Some data demonstrates that this school's market-based argument resonated with state authorities, while other data indicates that this market-based argument coincided with the state's own interest to defend its legitimacy in policymaking.